PERANAN PEREMPUAN DALAM DAKWAH DI PULAU SERIBU MASJID - Syarifudin, Amir (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2023)
This article is aimed to know the women’s role in dakwah. According to islam, men and women have an equal right such as in worship, education, social, family, and no exception in dakwah. Which are now days are dominated by men. Islam is really respect and honor the women and so far, Allah named his surah in Qur’an by Annisa which means “Women”. Women have special skills and techniques in delivering Amar M’aruf Nahi Munkar especially to other women because there are some materials which are related to women only and not appropriate to be delivered by men such as haid, Istihadah, Nifas, and others. These kinds of problems are known and done by women only. There for women are expected to be more contribution in dakwah, so the massages of Diin can be delivered faster and no women left behind.